Preparation of multi-allylic dendronized polymers via atom-transfer radical polymerization. (September 2019) - Schwartz, Pierre-Olivier; Moingeon, Firmin; Roeser, Jérôme; Couzigné, Emilie; Voirin, Emilie; Masson, Patrick; Méry, Stéphane
Graphical abstract: Highlights: Use of ATRP to prepare multiallyl-branched polymers. Preparation of multifunctional polymers with low polydispersity value ( Ð ≤ 1.25). Significant slowdown of the propagation due to bulkiness of the radical species. Apparent saturation of the polymer growth reached for DP ≈ 25–30. Precursory polymers towards wormlike structures with tailorable functionalities. Abstract: Atom-transfer radical polymerization (ATRP) was investigated to polymerize a styrene monomer carrying carbosilane dendrons with 6 terminal allyl branches. Polymers with a monomodal molar mass distribution and low polydispersity have been produced, while by comparison the free-radical polymerization technique led to chain transfer early in the polymerization. Steric effect brought by the dendrons result in a slow polymerization rate, leading to an apparent saturation of the degree of polymerization. By pushing up the polymerization conditions (eg. increase of temperature or concentration), interchain couplings started to take place, most likely from reactions at the allyl branches. These results are very similar to the ones previously reported for the anionic polymerization of this same multi-allylic dendronized monomer.